Assessing the cardiovascular and potassium lowering effects of levalbuterol compared to albuterol: a randomized control trial - Shebli, Baraa; Ghabally, Mike; Shabouk, Muhammad Besher; Arnaout, Ahmad Yamen; Zeina, Mohamed Besher; Malhis, Mahmoud (Frontiers in Cardiovascular Medicine, 2025)
BackgroundBeta-agonists like Levalbuterol and Albuterol are used in the treatment of Hyperkalemia. However, few studies in the medical literature have directly compared the cardiac effects and potassium-lowering efficacy of levalbuterol and albuterol, yielding inconclusive results. Understanding the cardiovascular effects and potassium-lowering abilities of these medications in hyperkalemic patients is crucial for optimizing treatment strategies and minimizing adverse events.MethodsThis randomized controlled trial conducted at Aleppo University Hospital in Syria aimed to compare the cardiovascular and potassium-lowering effects of Levalbuterol vs. Albuterol in hyperkalemic patients. The study, carried out between October 2021 and February 2022, utilized a single-center single-blinded two-armed design with patients randomized using a computer-generated sequence and block randomization method.ResultsThe results showed no significant difference in mean HR change between Levalbuterol and Albuterol groups at 30 min, nor in the change in potassium serum levels at 90 min. Both drugs exhibited similar patterns in HR changes over time and blood pressure variations at different points. Despite limitations in data collection for side effects, the reported symptoms in both groups were consistent with known side effects of beta-agonists, with tremors and nervousness being the most commonly reported.ConclusionOur study provides the first direct insights into the effects of Levalbuterol and Albuterol on heart rate, potassium levels, and blood pressure which would be very important in specific cases such as in patients with heart failure. Both medications showed similar patterns in heart rate changes, potassium levels, and blood pressure variations at different time points.Clinical Trial RegistrationClinicaltrials.gov, identifier NCT05173584.